1992
DOI: 10.1007/bf02047878
|View full text |Cite
|
Sign up to set email alerts
|

Healing of ischemic colonic anastomosis

Abstract: Fibrin adhesives have been advocated as a protective sealant in high-risk colonic anastomoses to prevent leakage. To assess the effect of fibrin glue sealing on the healing ischemic anastomosis, we compared the healing of sutured colonic anastomoses in the rat, with and without fibrin adhesive (Groups IA and IB), and ischemic anastomoses with and without fibrin adhesive (Groups IIA and IIB). On days two, four, and seven, 10 animals in each group were sacrificed. Adhesion formation was scored, and the in situ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Of the 8 studies with no effect on healing, 6 studies revealed a positive effect on bursting pressure or anastomotic strength [70,75,76,77,78,80]. Similar findings were seen in the group of studies reporting a negative effect on healing, where 1 study found a positive effect on bursting pressure and anastomotic strength [63], 6 studies found no effect on these mechanical end points [62,64,65,66,67,68] and only 1 study found a negative effect on bursting pressure [69]. On the contrary, all of the 7 studies that reported a positive effect on healing also showed a positive effect on the mechanical end points [55,56,57,58,59,60,61].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Of the 8 studies with no effect on healing, 6 studies revealed a positive effect on bursting pressure or anastomotic strength [70,75,76,77,78,80]. Similar findings were seen in the group of studies reporting a negative effect on healing, where 1 study found a positive effect on bursting pressure and anastomotic strength [63], 6 studies found no effect on these mechanical end points [62,64,65,66,67,68] and only 1 study found a negative effect on bursting pressure [69]. On the contrary, all of the 7 studies that reported a positive effect on healing also showed a positive effect on the mechanical end points [55,56,57,58,59,60,61].…”
Section: Discussionsupporting
confidence: 69%
“…In 7 of the 28 studies, a positive effect of FG on healing was found [55,56,57,58,59,60,61], while 8 studies reported a negative effect [62,63,64,65,66,67,68,69] and 11 studies found no effect [54,70,71,72,73,74,75,76,77,78,79]. Furthermore, 2 studies reported unclear results [80,81] (table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This simulates both the clinical situation with a defect in the stapler line or an insufficiently handsewn anastomosis. Ischemia is created by devascularizing the anastomotic edges by removing mesenteric vessels [24]. This is a good approximation to the clinical situation where removal of mesentery is often necessary for mobilization of the intestine, or where insufficient blood flow for other reasons may contribute to local ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the anastomotic bursting pressure being almost 0 for the incomplete anastomoses, no leakage of the colonic content occurred to cause peritonitis. Evaluating ischemia of the rat anastomosis, the same authors created a model by coagulating 2 cm of mesenteric vessels on each side of the anastomosis and thereby compromising blood supply [24]. The anastomosis was created with 12 interrupted nonabsorbable sutures and the same level of the colon as in the previous study was used.…”
Section: Animalsmentioning
confidence: 99%